Tectonic Keratoplasty to Restore the Bulbar Wall after Block Excision of Benign and Malignant Intraocular Tumors. (2nd May 2019) - Balestrazzi, Emilio; Mosca, Luigi; Blasi, Maria Antonietta; Giannico, Maria Ilaria; Balestrazzi, Angelo
Abstract : Purpose . To report the surgical treatment and follow-up of tumors of the anterior uvea and epithelial cysts of the anterior chamber in 4 patients submitted to block excision and tectonic corneal graft between 2008 and 2012. Methods . This is a retrospective, nonrandomized case series. Two patients were affected by anterior uveal malignant melanoma, and 2 patients were referred to us for large epithelial iris cysts with anterior chamber angle involvement and partial corneal failure. A simultaneous block removal of the lesion and adjacent iris, cornea (when necessary), ciliary body, and sclera was performed; the resulting defect was covered by a tectonic whole thickness corneal graft. Follow-up ranged from 2 to 7 years (mean time: 5 ± 1.6 MD). Results . Local control of malignant melanoma was observed during the follow-up, but cataract surgery was planned in both patients and pars plana vitrectomy for vitreous hemorrhage occurred in one case. No recurrence of cysts was detected. After iris cysts excision, a planned second-time surgery was necessary in one patient: optical penetrating keratoplasty, centered on the visual axis, implantation of one refractive IOL (intraocular lens) in the bag, and one cosmetic IOL in the sulcus, to restore the iris diaphragm. Conclusions . Block excision followed by the tectonic corneal graft seems to be the treatment of choice for selected cases of epithelial cysts of the anterior chamber and anterior uvea melanomas with epibulbar extension. Further surgery, as a second step, could be required to improve functional results of this challenging technique.